The empowerment of the educational concept of spiritual rehabilitation of muslim prisoners in Singapore Prison - Shahar, Shariff Mohd; Zamsiswaya; Bte Salman, Nola Fibriyani (Tawazun: Jurnal Pendidikan Islam, 2023)
The Singapore government pays considerable attention to rehabilitation programs for prison inmates. The programs have proven to be influential in keeping recidivism rates relatively low. Muslim prisoners are no exception. Although not all of them are willing to change, the right concept of rehabilitation can motivate prisoners to rebuild their lives. This research tries to offer the concept of religious-based rehabilitation education for Muslim prisoners through Islamic education. The research method used is a qualitative method using a qualitative descriptive approach. The type of research is case study research by focuses on a literature review. The data used is taken from documents related to rehabilitation activities in prisons that have occurred and scientific research that has been done before. The results suggest that there are four important foundations in the concept of religious-based rehabilitation education for Muslim prisoners in Singapore prisons. The four foundations are the purpose of the concept, the program or curriculum of the rehabilitation education program, the process of the rehabilitation program, and finally the evaluation of all the programs that have been developed. Abstrak Pemerintah Singapura memberi perhatian yang cukup baik pada program rehabilitasi para narapidana di penjara. Program-programnya terbukti dapat mempengaruhi dalam menjaga tingkat residivisme kembali berbuat jahat menjadi relatif rendah. Tak terkecuali dengan para narapidana muslim. Meskipun tidak semua dari mereka bersedia untuk berubah, namun dengan konsep rehabilitasi yang tepat dapat memotivasi narapidana untuk membangun kembali kehidupan mereka. Penelitian ini mencoba menawarkan konsep pendidikan rehabilitasi berbasis religius untuk para narapidana muslim melalui pendidikan Islam. Metode penelitian yang digunakan adalah metode kualitatif dengan menggunakan pendekatan deskriptif kualitatif. Jenis penelitiannya adalah penelitian studi kasus dengan memfokuskan penelitian pada kajian pustaka pustaka. Data-data yang digunakan diambil dari dokumen-dokumen yang terkait dengan kegiatan rehabilitasi di penjara yang sudah terjadi dan penelitian-penelitian ilmiah yang telah dilakukan sebelumnya. Hasil penelitian menawarkan ada empat pondasi penting dalam sebuah konsep pendidikan rehabilitasi berbasis religius untuk para narapidana muslim di penjara Singapura. Empat pondasi itu adalah tujuan konsep itu dibuat, program atau kurikulum dari program pendidikan rehabiltasi tersebut, proses dari program rehabilitasi, dan terakhir evaluasi dari semua program-program yang telah disusun.